Collagen matrix biofunctionalized with injectable platelet-rich fibrin for the treatment of single gingival recession: A case report - Santamaria, Mauro Pedrine [UNESP]; Rossato, Amanda [UNESP]; Ferraz, Lais Fernanda Ferreira [UNESP]; Bonafe, Ana Carolina [UNESP]; Miguel, Manuela Maria Viana [UNESP]; Nunes, Marcelo Pereira (Wiley-Blackwell, 2022)
Introduction Collagen matrices have been used as connective tissue graft (CTG) substitutes. However, they do not have the same efficacy compared to CTG. Adding biological agents may increase collagen matrices' efficacy. The present case reports the use of a biofunctionalized volume-stable collagen matrix (VCMX) with injectable platelet-rich fibrin (iPRF) associated with the coronally advanced flap (CAF) to treat single gingival recession (GR) defect. Case Presentation A Recession Type 1 (RT1 A-) defect at maxillary left canine in a male patient was treated using a VCMX biofunctionalized with iPRF associated with CAF. No swelling or edema was observed during the first 14 days after surgery. Complete root coverage was observed (RecRed of 4.0 mm) after 6 months. Gingival thickness (GT) increased (1.0 mm) by the end of the follow-up. Conclusion The present case report shows that CAF associated with VCMX+iPRF presents good clinical outcomes for single GR defect. Key points Why is this case new information? This case is the first one to our knowledge to describe the biofunctionalization of VCMX with iPRF to treat single gingival recession. What are the keys to successful management of this case? Proper material handling. Proper iPRF protocol execution. What are the primary limitations to success in this case? Need of venipuncture. Correct preparation of VCMX+iPRF. Patient compliance.
Keywords: Dental; Esthetics; Gingival recession; Tooth cervix